2023
DOI: 10.3390/app13020851
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Median Opening Length of a Freeway Work Zone Based on a Naturalistic Driving Experiment

Abstract: Median openings are an effective traffic organization mode for freeway crossover work zones, and their length is one of the most important control indicators to ensure traffic safety in work zones. In this paper, a theoretical calculation model of the median opening length was established according to the lane-changing demands of vehicles crossing through the median opening of the freeway. Based on the calculation model, the influencing factors of the median opening length were analyzed, and the calculation va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Based on the fuzzy evaluation matrix C calculated in Section 3.3 and the weights of each evaluation indicator i w determined in Section 3.4, the fuzzy comprehensive evaluation result B can be calculated according to Equation (10).…”
Section: Evaluation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fuzzy evaluation matrix C calculated in Section 3.3 and the weights of each evaluation indicator i w determined in Section 3.4, the fuzzy comprehensive evaluation result B can be calculated according to Equation (10).…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…A shorter median opening length reduces the turning radius for vehicles, potentially reducing their speed and increasing the risk of accidents, such as tailgating. Conversely, a longer median opening length increases the maximum deceleration speed, resulting in higher speed changes at the opening, compromising both driving safety and comfort [3][4][5] .To determine the appropriate length of the median opening, scholars have analyzed the force situation and trajectory characteristics of vehicles driving through the median opening conversion section [6][7][8][9][10][11][12] . They have established a calculation model based on traffic flow theory, circular curve lane change trajectory model, and 5 times polynomial lane change model.…”
Section: Introductionmentioning
confidence: 99%
“…It is reliable and easy to measure, and it can be adopted to measure the driving workload. When drivers are stressed or fatigued, their heart rate will change; the HRV index can characterize the change in heartbeat cycle variability, which, in turn, reflects a driver's driving stress and fatigue [31,33]. The measurement model of the driving workload is shown in Equation (1):…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the standard freeway section, the conditions of the road, traffic, and environment in the affected area of the tunnel change drastically. The stimulation of drivers in the affected area of the tunnel is different from that of other road sections; the physiological and psychological changes that drivers experience during driving in the affected area of the tunnel are the driving workload [31]. Different tunnel lengths will have different impacts on drivers; at present, the impact of different categories of tunnels on driver safety, comfort, and driving behavior under naturalistic driving conditions is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have evaluated the impact of road construction through dynamic traffic allocation and compared alternative construction schedule plans in order to choose the optimal plan to reduce travel delays and improve road capacity [10,11]. Several studies have analyzed the impact of construction work zone length on road capacity [12][13][14]. In addition, scholars have found that a work zone located at the intersection causes deviation of the road, which in turn leads to deviation of the main traffic flow, and have proposed two road improvement plans for this purpose [15].…”
Section: Introductionmentioning
confidence: 99%